Assessment of oral health status according to the international index OHAT (Oral Health Assessment Tool) - T. G. Petrova; N. B. Borodina; O. S. Gileva; T. V. Libik; O. V. Dunicheva (Сибирский научный медицинский журнал, 2025)
The international Oral Health Assessment Tool (OHAT) index in its relevant language versions is widely used in dentistry and medicine in many countries around the world to determine the level of oral health and assess the effectiveness of medical interventions.   The aim of the study was to develop, determine the validity and reliability of the Russian-language version of the OHAT.   Material and methods. The study involved 148 elderly and senile individuals hospitalized in the emergency cardiology department. During the study, the feasibility, inter-expert reliability, and stability of the tool for assessing oral health were evaluated.   Results. When using the OHAT, the evaluation of oral health status across specific domains and the pain parameter, as well as the scoring process, did not cause any difficulties. The formulations proposed in the OHAT index were found to be clear, correct and unambiguous. The most frequently identified deviations in health status (2 scores) were recorded for the parameters of “natural teeth” – 30,19 %, “dentures” – 21,28 %, and “oral hygiene” – 16,4 %. The average OHAT index value for patients was 3.38 ± 0.16 scores indicating a level of loss of dental health in elderly individuals. The agreement among experts ranged from an average for the parameters of “oral hygiene” (84.90 %) and “tongue” (85.85 %) to a high for the parameter “dental pain” (98.11 %). The Cohen’s kappa coefficient for the experts’ responses was in the range of good agreement (0.61–0.80) for the parameter’s “tongue”, “saliva”, “oral hygiene” and in the range of excellent agreement (0.81–1.0) for all other analyzed parameters. The correlation coefficient for the total score of expert responses was 0.949 (p < 0.05), indicating very high inter-rater reliability.   Conclusions. The results of the study confirm that the Russian-language version of the OHAT index is a valid and reliable tool for the screening assessment of oral health by healthcare providers without dental training. The absence of a need for special conditions to determine the index, as well as its applicability by specialists without dental education, significantly increases potential of index use.